Homeobox B9 Promotes the Progression of Hepatocellular Carcinoma via TGF-β1/Smad and ERK1/2 Signaling Pathways. (16th September 2022) - Bai, Lizhi; Ge, Pan; Zhang, Yanni; Song, Yi; Xing, Rong; Zhou, Dangxia
Abstract : Objectives . Homeobox B9 (HOXB9), a homeodomain-containing transcription factor, may play a role in hepatocellular carcinoma (HCC) progression. However, the exact mechanisms underlying its action remain unclear. Materials and methods . Immunohistochemistry was used to investigate the expression of HOBX9 and its prognostic values in HCC patients. HCC cells were transfected with pBabe-HOXB9 and shHOXB9 plasmids, and MTT assay, Transwell assays, and xenograft mouse models were employed to determine the effects of HOXB9 on HCC cell proliferation, migration, and invasion in vitro and in vivo . The biological mechanisms involved in the role of HOXB9 were determined with Western blot and RT-qPCR methods. Results . HOXB9 expression was significantly increased in HCC tissues and cell lines. Patients with higher HOXB9 levels were associated with poor prognosis. Overexpression of HOXB9 in BEL-7405 cells promoted proliferation, migration, and invasion, whereas knockdown of HOXB9 in HepG2 cells significantly reduced cell proliferation, migration, and invasion abilities. Mechanically, a positive correlation was found between HOXB9 expression and transforming growth factor- β 1 (TGF- β 1) and extracellular signal-regulated kinase (ERK)1/2 pathway in HCC tissues. HOXB9 overexpression stimulated TGF- β 1/Smads signaling pathway in BEL-7405 cells. In contrast, HOXB9 knockdown inhibited the TGF- β 1/Smads signaling pathway in HepG2 cells. In addition, the treatment with TGF- β 1 inhibitor, LY364947, significantly reserved HOXB9 overexpression-induced cell proliferation, migration, and invasion abilities. Conclusions . These findings validated that HOXB9 promoted proliferation, migration, and invasion in HCC cells by stimulating the TGF- β 1/Smads and ERK1/2 signaling pathway. HOXB9 could be a promising prognostic biomarker and a potential therapeutic target in HCC.